Improving clinical paediatric research and learning from COVID-19 - Ramanan, Athimalaipet V. (2022)
Funding Information: Competing interests: A.V.R. has received Speaker fees/Consultant for Abbvie, Novartis, UCB, SOBI, Eli Lilly and Roche. N.M. reports grants outside the submitted work in the last five years from the Medical Research Council, National Institute of Health Research, March of Dimes, British Heart Foundation, HCA international, Health Data Research UK, Shire Pharmaceuticals, Chiesi Pharmaceuticals, Prolacta Life Sciences, and Westminster Children’s Research Fund; N.M. is a member of the Nestle Scientific Advisory Board and accepts no personal remuneration for this role. N.M. reports travel and accommodation reimbursements from Chiesi, Nestle and Shire. N.M. is a member of C4C, International Neonatal Collaboration (INC), UK National Research Ethics Advisory Service and MHRA advisory groups and/or working parties. S.W. has received compensation as a member of the scientific advisory board of AM Pharma, Novartis and Khondrion and receives research funding from IMI2 for the Conect4children project. B.A. has worked for GlaxoSmithKline between October 2006 and September 2009 and holds company shares. Between October 2009 and May 2015, she has worked for Novartis. M.S. has recieved research grant and honoraria for meetings and Advisory Boards from Alexion, Sanofi/Genzyme, Takeda, CHIESI, Ultragenix, Orchard, Orphazyme. P.I. is a permanent employee of Bayer AG, Germany. M.V. has received compensation for Advisory boards or Steering committes from Roche, Novartis, Achillion, Apellis, Retrophin/Travere, Alexion pharmaceuticals. C.M. has been a consultant to or has received honoraria from Janssen, Angelini, Servier, Nuvelution, Otsuka, Lundbeck, Pfizer, Neuraxpharm and Esteve outside the submitted work. She declares conflicts of interest unrelated to the present work. M.C. had advisory roles for AstraZeneca, Bayer, Bristol Myers Squibb, Eisai, Lilly, and Roche in the last 2 years (outside the topic of the submitted work, for oncology drugs). M.J. has received research grants from Shire and has been engaged as a speaker or consultant by Shire, Ginsana, PCM Scientific Evolan, and New Nordic, all unrelated to the present work. P.S. has received speaker fees and participated at advisory boards for Biomarin, Zogenyx, GW Pharmaceuticals, and has received research funding by ENECTA BV, GW Pharmaceuticals, Kolfarma srl., Eisai. E.R. has received speaker fees and participated at advisory boards for Eisai and has received research funding by GW Pharmaceuticals, Pfizer, Italian Ministry of Health (MoH) and the Italian Medicine Agency (AIFA). This work was developed within the framework of the DINOGMI Department of Excellence of MIUR 2018-2022 (legge 232 del 2016). M.A.R. is a member of the c4c Ethics Expert Group and received compensation for ethical consulting activities from Bayer AG Wallace Crandall is employee of Eli Lilly and Co. P.C. is an employee of UCB, and owns stock in the company. She was previously an employee of GSK and owns stock in the company. N.R. has received honoraria for consultancies or speaker bureaus from the following pharmaceutical companies in the past 3 years: Ablynx, Amgen, Astrazeneca-Medimmune, Aurinia, Bayer, Bristol Myers and Squibb, Cambridge Healthcare Research (CHR), Celgene, Domain therapeutic, Eli-Lilly, EMD Serono, Glaxo Smith and Kline, Idorsia, Janssen, Novartis, Pfizer, Sobi, UCB. The IRCCS Istituto Giannina Gaslini (IGG), where NR works as full-time public employee has received contributions from the following industries in the last 3 years: Bristol Myers and Squibb, Eli-Lilly, F Hoffmann-La Roche, Novartis, Pfizer, Sobi. This funding has been reinvested for the research activities of the hospital in a fully independent manner, without any commitment with third parties. M.L. receives/has received consultation fees from CSL Behring, Novartis, Roche and Octopharma, travel grants from Merck Serono, and been awarded educational grants to organise meetings by Novartis, Biogen Idec, Merck Serono and Bayer. All other authors have no disclosures. Funding Information: Conect4children has received funding from the Innovative Medicines Initiative 2 Joint Undertaking under grant agreement No 777389. The Joint Undertaking receives support from the European Union’s Horizon 2020 research and innovation programme and EFPIA. The views expressed in this article are the personal views of the author(s) and should not be interpreted as made on behalf of, or reflecting the position of, the regulatory agency/agencies or organisations with which the author(s) is/are employed/affiliated . Publisher Copyright: © 2021, The Author(s).